Oral immunization against Helicobacter pylori. - Czinn, S J (1991)
Helicobacter pylori, which has been associated with gastritis and duodenal ulcers, commonly chronically infects adults. Eradication of this microorganism, which is difficult to achieve, results in normalization of gastritis and marked reduction in the relapse rate of duodenal ulcers. Since eradication is difficult to achieve, prevention of initial colonization of the gastrointestinal tract may be a viable alternative for abrogation of H. pylori-associated gastroduodenal disease. To test the feasibility of this approach, mice and ferrets were orally immunized with killed H. pylori. Immunization induced immunoglobulin A and G anti-H. pylori antibodies in both gastrointestinal secretions and sera of mice. These responses were enhanced when cholera toxin was included in the immunization protocol as a mucosal adjuvant. In ferrets, addition of cholera toxin resulted in significant enhancement of anti-H. pylori antibody levels in sera and intestines. Thus, oral immunization with killed H. pylori may be feasible approach to protect hosts from this infection and the accompanying gastroduodenal disease.